Rice diseases in Malaysia: a review on containment and control strategies / Nazaruddin Omar - Omar, Nazaruddin (Faculty of Plantation and Agrotechnology, 2016)
The purpose of this study is to review on rice diseases in Malaysia in term of its containment and control strategies applied among the paddy farmers. Besides that, the major rice diseases reported in Malaysia there are rice tungro disease (RTD) or known as 'penyakit merah' caused by tungro virus, blast disease caused by fungal pathogen Magnaporthe oryzae, bacterial Xanthomonas oryzae is the causal pathogen of the blight disease and rice sheath blight caused by Rhizoctonia solani Paddy or rice is important sources of food that cover a population of 30 Million citizens in Malaysia. Nowadays, the problems situation among farmers in Malaysia that most depend on the use of the chemical substance to control and prevent the disease that develops high cost and also effects the environment. Based on the study can expose to the farmer on how to control the major diseases damaged the paddy field in Malaysia that do not affect the environment and save cost to manage the diseases. Besides that, use of the cultural method, biological method, and resistance planting material can be applied to overcome the problems and decrease use of chemical substances. Moreover, the farmers in Malaysia preferred to use of inputs such as fertilizers and pesticides that including insecticides, herbicides, and fungicides in their crop plantation areas through farming community of the county in the previous decades. However, based on this study also gave information of method that proposed by the government organization in Malaysia there are Malaysian Agricultural Research and Development Institute (MARDI), Muda Agricultural Development Authority (MADA), Ministry of Agriculture and Agro-Based Industry Malaysia (MOA) and Integrated Agricultural Development Area (IADA) that provide updated information about how to control and manage the diseases among farmers in Malaysia.